1997
DOI: 10.1007/s11357-997-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

A circadian study of liver antioxidant enzyme systems of female Fischer-344 rats subjected to dietary restriction for six weeks.

Abstract: We examined the influences of dietary restriction (DR) on the circadian profile of liver catalase (CAT), glutathione peroxidase (GPx), and interacting systems required for removal of H2O2 (support systems), in 18-week old female Fischer 344 rats fed 60% of their ad libitum (AL) diet for six weeks. Food was presented to the DR animals during the early light-span. Regardless of diet, enzyme levels were generally consistent with circadian patterns. In CR animals, maximum activities often occurred at the time of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…9 However, this steady state level of ROS may increase with age as antioxidant systems are compromised. 10 For example, it has been shown that quantitative and qualitative activities of glucose 6-phosphate dehydrogenase, glutathione peroxidase, and catalase are compromised with age, 11,12 and in such oxidatively active tissues as skeletal muscle, antioxidant enzyme systems are induced within the mitochondrial fraction. 13 Ames 14 has estimated that the number of oxidative lesions per cell per day to the DNA may be as high as 100,000 in the rat.…”
mentioning
confidence: 99%
“…9 However, this steady state level of ROS may increase with age as antioxidant systems are compromised. 10 For example, it has been shown that quantitative and qualitative activities of glucose 6-phosphate dehydrogenase, glutathione peroxidase, and catalase are compromised with age, 11,12 and in such oxidatively active tissues as skeletal muscle, antioxidant enzyme systems are induced within the mitochondrial fraction. 13 Ames 14 has estimated that the number of oxidative lesions per cell per day to the DNA may be as high as 100,000 in the rat.…”
mentioning
confidence: 99%